Evaluating Cervical Sagittal Alignment in Cervical Myelopathy: Are Sitting Cervical Radiographs and Standing Whole-Spine Radiographs Equally Useful?. Issue 6 (September 2019) - Morimoto, Yasuhiko; Shigematsu, Hideki; Iwata, Eiichiro; Tanaka, Masato; Okuda, Akinori; Masuda, Keisuke; Yamamoto, Yusuke; Takeshima, Toshichika; Nakagawa, Yoshiyuki; Tanaka, Yasuhito
Study Design: Retrospective review of medical charts and radiographic data. Objectives: We aimed to clarify the differences in cervical alignment findings between sitting cervical lateral radiographs and standing whole-spine lateral radiographs with clavicle positioning in cervical spondylotic myelopathy (CSM) patients. Methods: We retrospectively evaluated the radiographs of 50 consecutive patients who underwent cervical surgery for CSM in our hospital. Cervical sagittal alignment was evaluated based on the C0-2 angles and C2-7 Gore and Cobb angles. Head position was evaluated in terms of the center of gravity of the head to C7 (CGH-C7) angle and the McGregor angle (ie, the angle between the McGregor line and a horizontal line). The T1-slope was also evaluated. Results: The mean values of the CGH-C7 angle and T1-slope were significantly lower, while the mean value of the McGregor angle was significantly higher on whole-spine lateral radiographs with clavicle positioning than on sitting cervical lateral radiographs. The mean values of the C0-2 and C2-7 angles did not differ significantly between the 2 radiographic positioning approaches. Conclusions: Using whole-spine lateral radiographs with clavicle positioning may result in a significantly lower T1-slope and a posterior tilt of the head. In the absence of a compensatory change in cervical alignment, clavicle positioning may force patients to adopt an upward gazing position of the head. These compensatory mechanisms should be considered while evaluating cervical alignment on whole-spine lateral radiographs with clavicle positioning. Surgical planning should take into account the effect of posture on the radiographic appearance of cervical alignment.